The effect of Atlantic salmon consumption on the cognitive performance of preschool children – A randomized controlled trial. Issue 6 (December 2019) - Demmelmair, Hans; Øyen, Jannike; Pickert, Tina; Rauh-Pfeiffer, Astrid; Stormark, Kjell Morten; Graff, Ingvild Eide; Lie, Øyvind; Kjellevold, Marian; Koletzko, Berthold
Summary: Background and aims: Long chain polyunsaturated n-3 fatty acids (LC-PUFA) are of functional and structural importance for brain development. Observational studies have shown positive relations between fatty fish consumption and cognitive performance in children, but Results from intervention studies using supplementary n-3 LC-PUFA are conflicting. Salmon is a good source of n-3 LC-PUFA, including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). We tested the hypothesis that an increased dietary salmon intake results in better cognitive outcomes than a meat based diet. Methods: Children (n = 205, age 4–6 years) in this trial were individually randomized to eating meals containing farmed Atlantic salmon or meat three times weekly for 16 weeks. Pre- and post-intervention a cognitive test (Wechsler Preschool and Primary Scale of Intelligence, 3rd edition, WPPSI-III) and a fine-motor coordination test (Nine Hole Peg Test, 9-HPT) were performed. Biochemical analyses included glycerophospholipid fatty acid profiles in plasma and cheek cells, serum 25-hydroxyvitamin D, and urinary iodine concentration. Dietary intake before and during the study were determined using food frequency questionnaires. Results: Intakes of EPA, DHA, vitamin D and iodine were higher in the salmon than the meat group, but on biomarker level only EPA and DHA increased significantly in the salmon group compared to the meat group (p < 0.001). In general linear models no significant differences between the intervention groups were found in the scale scores of the WPPSI-III tests and the 9-HPT. In analyses of the raw scores, the salmon group showed significantly better improvement in two of the eight raw scores compared to the meat group (symbol search p = 0.038, picture concepts p = 0.047). Conclusions: Intake of farmed Atlantic salmon led to a greater increase of the raw scores of the picture concept and symbol search subtests, while in the six other subtests raw scores were not different between the groups. This might indicate a modest positive association of salmon intake with the performance of preschool children in some subtests evaluating fluid intelligence but does not suggest an influence on global IQ development. Clinical trial registry number and website: ClinicalTrials.gov registration number: NCT01951937 .